Representações sociais sobre a transexualidade para universitários : da patologização à diversidade sexual - Silva, Matheus Henrique Cardoso da (2023)
Transsexuality is a relevant topic for psychology studies because it is a current issue that needs a look focused on the recognition and affirmation of this gender identity. It is understood that transsexuality is characterized from the field of sexual and gender diversity, however, for a long time it was present in the main diagnostic and classificatory manuals of health, being treated as a mental disorder. Therefore, the pathologization of transsexual identities is understood as a manifestation of prejudice against this population. Thus, the objective was to analyze the social representations that university students have about transsexuality, considering the levels of prejudice identified by this group. The Theory of Social Representations was used as a theoretical support for this study, which enables the recognition of the subjective dimension of individuals, as well as their cognitive aspects, which, in turn, interfere with attitudes, social practices and behaviors regarding the represented object. It consists of a descriptive research with a mixed approach, applied online with students from public and private university institutions in Brazil, with a total of 200 participants, who had an average age of 26 years (SD = 8.88) and a predominant age group of 18 to 23 years old, mostly residing in the Northeast region of Brazil, mostly identified as cisgender women. In addition, most recognize their sexuality as heterosexual. The most predominant area of knowledge among the participants is Humanities, most of which are university students from public institutions studying between the 7th and 10th period of graduation. The instruments used were: Socio-demographic questionnaire, analyzed through simple frequency calculation; the Free Association of Words Technique, analyzed with the help of the program Interface de R pour les Analyzes Multidimensionnelles de Textes et de Questionnaires (IRaMuTeQ); the Revised Prejudice Against Sexual and Gender Diversity Scale (PASGD-R); and closed questions about transsexuality, analyzed using descriptive and inferential statistics using SPSS. In addition, open questions were also used that were analyzed through Bardin's Thematic-Categorical Analysis. The results of the PASGD-R indicated low levels of prejudice against transsexuality by the study participants, with a variant between 1.27 and 1.63, and a variant standard deviation between 0.605 and 1.143. It was found that the students who participated in this study, for the most part, apprehend the phenomenon with a favorable view of transsexual identities, directing themselves to the recognition of gender identity. In addition, the sensitivity of the participants regarding the reality of transsexual people is highlighted when, for example, they are able to identify the obstacles that are faced by this community and also when they state that there is prejudice arising from society and suffered by this group and mention the repercussions of these difficulties on the socio-emotional life of the transsexual individual. In view of the results found, the importance of social changes in our society and the encouragement of representative spaces for transgender people is considered a relevant factor in the construction of social representations for individuals. It is believed that the data from this study can contribute to the development of more efficient strategies in the field of mental health and access to citizenship by the transsexual population, in addition to expanding spaces of representation, in order to promote the visibility of this group. It also highlights the need to create and maintain public policies that emphasize the guarantee of rights for this population, in order to remedy the psychosocial damage caused to this community.